Imported Flood‐Related Leptospirosis From Palau: Awareness of Risk Factors Leads to Early Treatment. Issue 6 (November 2015) - Matono, Takashi; Kutsuna, Satoshi; Koizumi, Nobuo; Fujiya, Yoshihiro; Takeshita, Nozomi; Hayakawa, Kayoko; Kanagawa, Shuzo; Kato, Yasuyuki; Ohmagari, Norio
<x xml:space="preserve">Abstract</x> We describe two Japanese travelers with leptospirosis who visited Palau. Both travelers swam in Ngardmau Falls, which was flooded for two days after typhoon Phanfone. The diagnoses were confirmed by microscopic agglutination test or polymerase chain reaction. This is the first report of leptospirosis in travelers who returned from Palau. It should be noted that choosing the appropriate test to biologically confirm leptospirosis was highly time‐dependent. Awareness of the risk factors for leptospirosis, mainly that of the exposure to contaminated fresh water after a flooding, would lead to an early and appropriate treatment before the confirmed diagnosis.